Antisense inhibition of lpxB gene expression in Acinetobacter baumannii by peptide–PNA conjugates and synergy with colistin. (5th October 2019) - Martínez-Guitián, Marta; Vázquez-Ucha, Juan Carlos; Álvarez-Fraga, Laura; Conde-Pérez, Kelly; Bou, Germán; Poza, Margarita; Beceiro, Alejandro
Abstract: Background: LpxB is an enzyme involved in the biosynthesis pathway of lipid A, a component of LPS. Objectives: To evaluate the lpxB gene in Acinetobacter baumannii as a potential therapeutic target and to propose antisense agents such as peptide nucleic acids (PNAs) as a tool to combat bacterial infection, either alone or in combination with known antimicrobial therapies. Methods: RNA-seq analysis of the A. baumannii ATCC 17978 strain in a murine pneumonia model was performed to study the in vivo expression of lpxB . Protein expression was studied in the presence or absence of anti- lpxB (KFF)3 K-PNA (pPNA). Time–kill curve analyses and protection assays of infected A549 cells were performed. The chequerboard technique was used to test for synergy between pPNA and colistin. A Galleria mellonella infection model was used to test the in vivo efficacy of pPNA. Results: The lpxB gene was overexpressed during pneumonia. Treatment with a specific pPNA inhibited LpxB expression in vitro, decreased survival of the ATCC 17978 strain and increased the survival rate of infected A549 cells. Synergy was observed between pPNA and colistin in colistin-susceptible strains. In vivo assays confirmed that a combination treatment of anti- lpxB pPNA and colistin was more effective than colistin in monotherapy. Conclusions: The lpxB gene is essential for A. baumannii survival. Anti- lpxB pPNA inhibits LpxB expression, causing bacterial death. This pPNA showed synergy with colistin and increased the survival rate in G. mellonella . The data suggest that antisense pPNA molecules blocking the lpxB gene could be used as antibacterial agents.